Graphene Flakes: Orientation Control of Graphene Flakes by Magnetic Field: Broad Device Applications of Macroscopically Aligned Graphene (Adv. Mater. 1/2017). Issue 1 (January 2017) - Lin, Feng; Zhu, Zhuan; Zhou, Xufeng; Qiu, Wenlan; Niu, Chao; Hu, Jonathan; Dahal, Keshab; Wang, Yanan; Zhao, Zhenhuan; Ren, Zhifeng; Litvinov, Dimitri; Liu, Zhaoping; et al.
Abstract : Writing letters with a suspension of graphene flakes and a magnet bar: the suspension is initially opaque due to randomly oriented graphene flakes, but the magnet's field makes it transparent by aligning the flakes. The graphene's diamagnetic and anisotropic absorptive properties make this writing board possible, as shown in article 1604453 by Z. M. Wang, J. M. Bao, and co‐workers.